THU0114 Abatacept as an effective treatment in the management of poor prognosis ACPA negative undifferentiated arthritis. (23rd January 2014) - Buch, M.H.; Freeston, J.E.; Rakieh, C.; Middleton, E.; Tan, A.L.; Pickles, D.; Ward, J.; Horton, S.; Das, S.; Wakefield, R.; Emery, P.
Abstract : Background: A goal in the management of undifferentiated arthritis (UA) is to prevent its progression to rheumatoid arthritis (RA). A preliminary study suggested abatacept may delay progression of ACPA positive UA to RA 1 . No therapy (including MTX) has been shown to be effective in ACPA negative patients however. Power Doppler (PD) on ultrasound (US) is a powerful predictive factor of persistent inflammatory arthritis in these patients 2 . Objectives: To evaluate whether Abatacept is effective in poor prognosis ACPA negative patients and its effect on US PD Methods: In this pilot, open-label, prospective study, patients with ACPA negative UA (≥2 joint synovitis) and PD ≥1 were recruited. Additional key inclusion criteria: symptom duration ≥3 months, ≤18 months and DMARD-naive. All patients receive 12 months of abatacept monotherapy. Primary endpoint is proportion of patients in DAS44 remission at 6 months. Clinical and US [Grey Scale (GS)/PD] assessments are undertaken at baseline, 6, 12, 18, 24 months. 20 joints are scanned, each assigned GS and PD score (maximum of 3); giving maximum totals scores of 60 for each. Descriptive and non-parametric statistics has been applied. Results: 20/23 patients screened were enrolled [15 female, 5 male; mean (SEM) age 53.2 (2.48) years, symptom duration 7.5 (0.9) months]. 19/20 and 13/20 have reached 6 and 12 months respectively. Significant median DAS44/DAS28 reduction was seen from baseline to 6 and 12 months (Table 1 ). At month 6, 6/19 (32%) achieved DAS28 remission; 5/19 (26%) DAS44 remission; at 12 months, 6/13 (46%; 1 missing value) achieved DAS28 remission; 5/13 (39%) DAS44 remission. Small GS and PD reduction was seen at 6 months but significant PD reduction at 12 months (Table 1 ). Of patients in remission the median (range) PD fell from 5 (2-23) at baseline to 1.0 (1-12) and 2.0 (0-8) at 6 and 12 months respectively. Table 2 details change in PD at 6 months based on baseline number of PD positive joints. Conclusions: This preliminary report suggests abatacept monotherapy confers clinical improvement in poor prognosis ACPA negative UA. It also demonstrates the ability of abatacept to reduce US PD signal, particularly in patients with higher baseline PD activity, consistent with higher burden of inflammatory disease. Complete data should provide additional insights. This study is supported by Bristol Myers Squibb. References: Emery P, et al. Impact of T-cell costimulation modulation in patients with undifferentiated inflammatory arthritis or very early rheumatoid arthritis: a clinical and imaging study of abatacept (the ADJUST trial). Ann Rheum Dis. 2010; 69(3):510-6. Freeston J, et al. A diagnostic algorithm for persistence of very early inflammatory arthritis: the utility of power Doppler ultrasound when added to conventional assessment tools. Ann rheum Dis 2010; 69(2):417-9. Disclosure of Interest: M. Buch Grant/Research support from: Bristol-Myers Squibb, Pfizer, Consultant for: Abbott, Roche, Bristol-Myers Squibb, J. Freeston: None Declared, C. Rakieh: None Declared, E. Middleton: None Declared, A. L. Tan: None Declared, D. Pickles: None Declared, J. Ward: None Declared, S. Horton: None Declared, S. Das: None Declared, R. Wakefield: None Declared, P. Emery Grant/Research support from: Bristol-Myers Squibb, Pfizer, Consultant for: Abbott, Roche, Bristol-Myers Squibb, Pfizer